MIGRAINE ASSOCIATION WITH ATRIAL SEPTAL DEFECT- a case report - Ristic, Daniela; Ristovski, Vladimir; Papazova, Marija; Dodevski, Ace (Journal of Morphological Sciences, 2018)
Migraine belongs to the group of primary headaches, in whose pathogenesis, despite the involvement of neurovascular, significant part, has the genetic factors, as well. The prevalence of migraine with aura in patients with atrial septal defect ranges from 11-22%.We present a case of a patient at the age of 28, with persistent headaches,18 months backwards. Headaches were usually preceded by phosphenescence, blurred vision, buzzing in both ears, nausea, feeling of tingling of the right hemicranium. An incomplete hour later severe headaches appeared, followed by tingling and a feeling of weakness on the left arm and lower extremities. Neurological examination was with left sided  paresthesias and hemiparesis. Routine biochemical examinations, hormone status, magnetic nuclear resonance of the brain and magnetic resonance angiography of intracranial vessels, cerebrospinal fluid analysis, and neurophysiological examinations was normal. At the transthoracic, and then transoesophageal echocardiography, was proved the presence of Atrial septal defect (ASD) in the central part of the interatrial septum. In the patient, an occlusion of ASD with ASD occluder was made, there was a reduction in the frequency of occurrence of migraine headaches. Controlled echocardiography was performed where the absence of the pre-established ASD occluder was observed in the aortic arch, where the removal of the dive (occlusion) was done and the closing of the ASD with a direct suture. A pathogenetic mechanism that explains the association of ASD / PFO with migraine is interatrial communication, which may result in the occurrence of paradoxical embolism and humoral factors of the pulmonary circulation.